Evolutionary History of the Poecilia picta Sex Chromosomes. (21st February 2023) - Fong, Lydia J M; Darolti, Iulia; Metzger, David C H; Morris, Jake; Lin, Yuying; Sandkam, Benjamin A; Mank, Judith E
Abstract: The degree of divergence between the sex chromosomes is not always proportional to their age. In poeciliids, four closely related species all exhibit a male heterogametic sex chromosome system on the same linkage group, yet show a remarkable diversity in X and Y divergence. In Poecilia reticulata and P. wingei, the sex chromosomes remain homomorphic, yet P. picta and P. parae have a highly degraded Y chromosome. To test alternative theories about the origin of their sex chromosomes, we used a combination of pedigrees and RNA-seq data from P. picta families in conjunction with DNA-seq data collected from P. reticulata, P. wingei, P. parae, and P. picta . Phylogenetic clustering analysis of X and Y orthologs, identified through segregation patterns, and their orthologous sequences in closely related species demonstrates a similar time of origin for both the P. picta and P. reticulata sex chromosomes. We next used k-mer analysis to identify shared ancestral Y sequence across all four species, suggesting a single origin to the sex chromosome system in this group. Together, our results provide key insights into the origin and evolution of the poeciliid Y chromosome and illustrate that the rate of sex chromosome divergence is often highly heterogenous, even over relatively short evolutionary time frames.